222k views
4 votes
6m-6=9m+15 (Show work)​

User Erosman
by
5.0k points

2 Answers

4 votes

Answer:

m = -7

Explanation:

  1. Combine like factors. It should now look like this: 6m - 9m = 6 + 15
  2. 6 + 15 = 21
  3. Plug 21 in: 6m - 9m = 21
  4. 6m - 9m = -3m
  5. Plug -3m in: -3m = 21
  6. Divide each side by -3 to cancel out the -3 next to x. It should now look like this: m = -7

I hope this helps!

User Adietisheim
by
5.1k points
1 vote

Answer:


m=-7

Explanation:


6m-6=9m+15

Add 6 to both sides:


6m-6+6=9m+15+6


6m=9m+21

Subtract 9m from both sides:


6m-9m=9m+21-9m


-3m=21

Divide both sides by -3:


(-3m)/(-3)=(21)/(-3)


m=-7

User Manzolo
by
5.4k points